Android-Based Articulate Storyline Interactive Media in IPAS Subjects - Amilatul Masrifah; Novi Setyasto (Postgraduate, University of Mataram, 2024)
The limitations of learning media, especially technology-based, make students passive so they feel bored and less interested in learning. This results in low student learning outcomes. This research aims to develop and test the feasibility, practicality, and effectiveness of Android-based interactive media in the IPAS subject, fifth grade elementary school interaction material. This type of research is developed using the Borg and Gall model. The data collection techniques used are observation, interviews, document data, tests, and questionnaires. The validation results by media expert validators were 91.3% and material experts were 91.2%, so an average of 91.25% met the valid criteria. Based on the pretest and posttest results, it is known that Android-based interactive media is effective in improving student learning outcomes as seen from the effectiveness of the t-test and N-gain tests. The t-test shows that Sig. < 0.05, meaning there is a significant difference between learning outcomes before and after treatment. The N-gain test shows a high criterion, namely 0.73 on a small scale, and a medium criterion, namely 0.59 on a large scale. Based on the results of the response questionnaire distributed, a very positive response was obtained from teachers and students. From these results, it can be concluded that Android-based interactive media is effective for improving the learning outcomes of IPAS as well as feasible and practical to use in the learning of fifth-grade elementary school students.